Bacillus subtilis PcrA Couples DNA Replication, Transcription, Recombination and Segregation - Moreno-del Alamo, María; Torres, Rubén; Manfredi, Candela; Ruiz-Masó, José A.; del Solar, Gloria; Alonso, Juan Carlos (Frontiers in Molecular Biosciences, 2020)
Bacillus subtilis PcrA abrogates replication-transcription conflicts in vivo and disrupts RecA nucleoprotein filaments in vitro. Inactivation of pcrA is lethal. We show that PcrA depletion lethality is suppressed by recJ (involved in end resection), recA (the recombinase) or mfd (transcription-coupled repair) inactivation, but not by inactivating end resection (addAB or recQ), positive and negative RecA modulators (rarA or recX and recU), or genes involved in the reactivation of a stalled RNA polymerase (recD2, helD, rapA and ywqA). We also report that B. subtilis mutations previously designated as recL16 actually map to the recO locus, and confirm that PcrA depletion lethality is suppressed by recO inactivation. The pcrA gene is epistatic to recA or mfd, but it is not epistatic to addAB, recJ, recQ, recO, rarA, recX, recU, recD2, helD, rapA or ywqA in response to DNA damage. PcrA depletion led to the accumulation of unsegregated chromosomes, and this defect is increased by recQ, rarA or recU inactivation. We propose that PcrA, which is crucial to maintain cell viability, is involved in different DNA transactions.